Psychological stress and cardiovascular risk among women in Brazilian communities: a cross-sectional study - Antônio José C. Mattos; Alvaro Avezum; João Italo D. França; Maria Cristina O. Izar; João Fernando M. Ferreira; Luciano Ferreira Drager; José Francisco K. Saraiva; Henrique Andrade R. Fonseca (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2024)
Abstract: Psychosocial evaluations are rarely conducted with community-dwelling individuals, especially those with higher risk of cardiovascular disease. This study aims to evaluate the perceptual stress and cardiovascular risk among women in a large cross-sectional study performed in Brazilian communities. Subjects aged over 18 years were included out of 500 public basic health units (BHU) in Brazil. All subjects were subjected to a clinical consultation and questionnaires application. Data were used to identify healthy lifestyle, smoking status, and self-perception of psychological stress. The National Health and Nutrition Examination Survey (NHANES) risk score (NRS) was used to estimate cardiovascular risk. Ethnicity information was self-reported, considering white versus non-white (black, brown, and mixed-race) women. A total of 93,605 patients were recruited from a primary care setting, of which 62,200 (66.4%) were women. Intense and severe auto-perception of stress was higher within non-white women at home (p < 0.001), at work (p = 0.008), socially (p < 0.001), and financially (p < 0.001) compared to white women. Therefore, the NRS indicates that non-white women had higher cardiovascular risk, lower physical activity, and lower daily vegetables/fruits consumption compared to white women (p < 0.001). Non-white women in Brazilian communities are susceptible to increased stress and cardiovascular disease risk, which adds up to disparities in access to the public health system.